The Effect Of Investment Knowledge, Motivation, Minimum Capital And Risk Perception On Student Investment Interest In The Faculty Of Economics And Business National University In Capital Markets - Hasanudin (International Publisher, 2023)
The goal of this study is to disentangle the effects of investing-related knowledge, investment motivation, required starting capital, and perceived risk. In 2019, 453 full-time students and employees enrolled in the Management Study Program participated in this study. This study used a non-probabilistic sampling method called purposive sampling, in which a predetermined set of criteria had to be met in order for the sample of 212 students to be selected. The data in this study was gathered by distributing questionnaires to students using data collection tools. Data analysis techniques such as the use of the Statistical Product and Service Solution (SPSS) software, version 23.0, for descriptive and inferential statistics based on multiple linear regression. Statistically significant positive effects of motivation, minimum capital, and perception of risk on investment interest were found in this study. This study also found a positive effect of investing knowledge on investment interest, although the effect was not statistically significant.